PENGARUH STRUKTUR MODAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Simangunsong, Endang Sepriani; Karamoy, Herman; Pusung, Rudy J. (Universitas Sam Ratulangi, 2018)
The Company was established not only to profit from the operations of the company. Getting profit is a short-term goal of a company. The main purpose and the long-term goal of a company is to maximize the company's wealth or value (value of the firm). The purpose of this study is to determine the effect of capital structure and institutional ownership of firm value on construction companies listed on the BEI period 2014-2016. Sampling method is by purposive sampling method. The sample of this research are 19 construction companies listed on BEI. The analysis tool used is multiple linear regression. The results showed that the capital structure has aÂ positive effect on firm value, which means that there is partially positive influence between capital structure variable to firm value. Partial institutional ownership does not have a positive effect on the value of companies in construction companies listed on the BEI period 2014-2016.Keywords: Capital Structure, Institutional ownership, value of the firm.